CLINICAL CASE OF ACUTE MYELOMONOBLASTIC LEUKEMIA - Суржикова, Галина Северьевна; Клочкова-Абельянц, Сатеник Аршавиловна; Зуева, Анна Валентиновна (Medicine in Kuzbass, 2025)
This article presents a clinical case of acute myelomonoblastic leukemia with development of marked infiltration of all organs and tissues by tumor cells. The diagnosis of AMMonL (M4) in patient K. was established on the basis of hematologic laboratory data, immunophenotyping results according to WHO criteria (2016).The presented clinical case demonstrates the need for an analytical approach to the evaluation of laboratory parameters of hematologic patients.
Keywords: acute myelomonoblastic leukemia; leukogram; blast cell immunophenotyping